COMPARISON OF STUDENTS' LEARNING OUTCOMES IN PHYSICAL EDUCATION TOWARDS CERTIFIED AND UNCERTIFIED TEACHERS AT SMA 1 KAMPAR - Leni Apriani; Ramadhan, Gibran (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aims to determine the comparison of student learning outcomes taught by certified teachers and uncertified teachers. The problem raised in this study is whether there is a significant difference in student learning outcomes based on teacher certification status. The method used is a quantitative method with a t-test, which is a type of statistical analysis used to test differences between two groups. The population in this study were all students in grades XI and XII of high school with a total of 551 students, consisting of 10 grades XI and 9 grades XII. Sampling was carried out by purposive sampling, namely by selecting one class from grade XI taught by uncertified teachers and one class from grade XII taught by certified teachers. Each class consists of 27 students, so the total research sample is 54 students. The instrument used to measure learning outcomes is student report card scores. Based on the results of descriptive statistics, it shows that the average value of students taught by certified teachers is 92.5185 with a 95% confidence interval indicating that the actual population average is likely to be between 91.6314 and 93.4056. While the average value of students taught by the teacher has not certification as big as 91.0370, with a 95% confidence interval indicating that the true population mean is likely to be between 89.1800 and 92.8941. The scores of students taught by certified teachers have higher average scores compared to the scores of students taught by non-certified teachers. Thus, it can be concluded that there is a significant difference in student learning outcomes based on teacher certification status.